2017
DOI: 10.1007/s40520-017-0847-z
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between clinical and radiographic evaluations of knee osteoarthritis

Abstract: BackgroundSignificant correlation has been previously demonstrated between radiographic and clinical diagnoses of knee osteoarthritis (OA); however, the specific findings on clinical examination that relate best to a radiographic diagnosis have not been fully elicited.AimsWe aimed to explore the relationship between clinical symptoms and physical findings with radiographic diagnoses of tibiofemoral and patellofemoral OA.MethodsThis study was based on 409 individuals from the Hertfordshire Cohort Study, born be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…Therefore, for clinically “certain” knees, diagnostic abilities based on clinical data only should be considered as good enough, in contrast to clinically “uncertain” knees. Our results support expert recommendations and the results of previous studies [ 3 , 4 , 6 , 7 , 8 ], where diagnoses based on clinical findings were found to be reliable and where radiographs were deemed unnecessary for diagnosing typical KOA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, for clinically “certain” knees, diagnostic abilities based on clinical data only should be considered as good enough, in contrast to clinically “uncertain” knees. Our results support expert recommendations and the results of previous studies [ 3 , 4 , 6 , 7 , 8 ], where diagnoses based on clinical findings were found to be reliable and where radiographs were deemed unnecessary for diagnosing typical KOA.…”
Section: Discussionsupporting
confidence: 90%
“…The European League Against Rheumatism Recommendations (EULAR) reported that three symptoms (knee pain, morning stiffness less than 30 min and functional limitation) combined with three clinical signs (crepitus, restricted range of motion and bone enlargement) could predict 99% radiographic KOA [ 3 ]. Similarly, recent studies showed that clinical manifestations, such as knee pain, crepitus, joint line tenderness, bony swelling and pain on flexion/extension could be used for identifying radiographic KOA [ 4 , 5 , 6 ]. Current recommendations advise not to use imaging in patients with typical OA presentations, but these were mainly based on expert opinion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a poor correlation between radiographic signs of knee OA and joint symptoms, which are relevant for the clinical diagnosis. In contrast with those findings, a general elderly population study showed positive association of radiographic knee OA with physical findings as determined by clinical examination, including tenderness, crepitus, pain on flexion, and bony swelling 40 . Radiographic OA was also found to be positively associated with knee pain, knee stiffness, and functional limitation.…”
Section: Cross-sectional Studiescontrasting
confidence: 71%
“…An alternative explanation could be that osteoarthritic joint damage could lead to overstimulation of mechanoreceptors, perhaps in the absence of clinical symptoms, as in the proposed AMI mechanism, eventually leading to reduced neural stimulation of muscle, alterations in muscle innervation, composition, and weakness. This mechanism is supported by the widely reported poor correlation of radiographic osteoarthritis with clinical symptoms, meaning that joint damage can occur in the absence of pain, and vice versa [29,30], though concordance has also been demonstrated [31].…”
Section: Discussionmentioning
confidence: 77%